Evaluation of Bioactive Components of Green- Lipped Mussel (GLM), Perna canaliculus, as a Modulator of Inflammatory Markers and Antioxidant Agent In Vitro - Cardim Lessa Teixeira, Roberta (Auckland University of Technology, 2023)
Chronic diseases, attributed to lifestyle changes, lack of physical activity, and unhealthy eating habits, have become a leading cause of global mortality. Traditional medicine is commonly employed for conditions like cancer, diabetes, autoimmune disorders, or cardiovascular diseases, often requiring prolonged medication use with potential side effects, affecting treatment effectiveness and adherence. Researchers are increasingly exploring nutraceuticals as natural adjuncts to conventional treatments. Among these, the green-lipped mussel biological extract has garnered attention for its potential to prevent and mitigate various pathological processes affecting human health. Notably, these creatures are rich in omega-3 polyunsaturated fatty acids (PUFAs), specifically eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), known to positively impact human health by enhancing joint health and cognitive function and reducing the risk of heart disease and metabolic disorders, as evidenced by numerous scientific studies. Increasingly prevalent chronic diseases, caused in part by lifestyle changes, have put great demand on natural products in recent years. There is no doubt that natural products have tremendous therapeutic potential. These products offer a range of benefits and provide safe and sustainable solutions to some of our most pressing health challenges. Therefore, the primary objective of this research was to determine the efficacy of a green-lipped mussel extract as an antioxidant and anti-inflammatory agent in vitro. Specifically, it was focused on establishing an extract capable of effectively and proficiently managing the inflammatory impacts on chondrocyte cells. To attain our goal, we implemented laboratory techniques to assess the efficacy of four compounds derived from green-lipped mussels through two distinct lipid extraction methods (Supercritical CO2 and organic solvent extraction). Two green-lipped mussel powders, one freshly prepared and another commercially available, were used to make the end compounds. The Thin-Layer Chromatography–Flame Ionization Detection (TLC-FID) method was used to conduct a comprehensive analysis of lipid classes in mussel extracts, while the Gas Chromatography-Mass Spectrometry (GC-MS) technique was employed to measure the free fatty acid content. They were meticulously evaluated for their potential as anti-inflammatory agents on activated immune cell lines and immunogenic stimulators to determine whether these extracts had positive effects at the molecular and cellular levels. Additionally, a human chondrocyte cell line was exposed to inflammatory stimuli to assess the extracts' effectiveness. The impact of the samples was assessed by analyzing reactive oxygen species, glucose uptake, and cytokine and MMP (matrix metalloproteinases protein) secretion in the cell supernatant. According to the research, solvent-extracted mussel oil could alleviate inflammation and boost the immune system by regulating cytokine secretion and modulating immune cell activation. On the other hand, samples extracted using supercritical CO2 showed a high release of cytokines despite having high levels of omega-3. Interestingly, the study also found that commercial powder extract of solvent-extracted mussel oil was more effective than fresh powder. It showed dose-dependent effects on TNF-α, interleukin-1β (IL-1β), and interleukin-2 (IL-2) cytokine secretion. As a result, the chondrocyte cell lines were tested using the samples generated by organic solvent extraction mentioned above. The results revealed that mussel oils generated through organic solvent extraction, particularly the commercial mussel powder extract, enhanced glucose uptake and protected chondrocyte cells. The sample effectively managed the release of inflammatory markers like interleukin-6 (IL-6) and matrix metalloproteinases-3 (MMP-3), showing increased deoxyglucose uptake. In conclusion, the data demonstrated that the green-lipped mussel extract could manage osteoarthritis. Based on the findings, it was possible to infer that the extract could stimulate immune cells, thereby improving the immune system. Furthermore, the extract displayed potential as a therapeutic agent for addressing biological processes that arise in inflamed joints and supporting the recovery of chondrocyte cells.